"Troponina e Peptídeo Natriurético tipo B no prognóstico da Estenose Valvular Aórtica" - Pedro Francisco Santos Madeira Guimarães Ramos (2018)
Background: aortic valve stenosis (AS) is an increasingly prevalent condition. Some patients with AS have increased plasma values of cardiac biomarkers. The aim of the present review was to analyze the prognostic value of major biomarkers in AS.  Methods: 11 articles regarding the potential use of Cardiac Troponin and B-type Natriuretic Peptide (BNP) in the prognosis of AS were identified.  Results: Both Troponin and BNP levels showed a correlation with myocardial structure and function as well as with morbidity/mortality, demonstrating prognostic utility in patients with AS. Conclusion: both biomarkers may be of use in managing patients with AS, namely in determining the optimal timing for surgical intervention. In fact, Cardiac Troponin and BNP have become useful tools in risk stratification and therapeutic management in AS patients, and both are readily available in clinical practice.